Susceptibility-Weighted Angiography Visualizes Hypoxia in Cerebral Veins. Issue 6 (June 2015) - Patzig, Maximilian; Feddersen, Berend; Haegler, Katrin; Olzowy, Bernhard; Mees, Klaus; Fischer, Rainald; Becker, Sven; Kisser, Ulrich; Freiherr, Jessica; Grashey, Rupert; Fesl, Gunther
Abstract : Objectives: The objective of this study was to evaluate the influence of short- and long-term hypoxia on the depiction of cerebral veins in the susceptibility-weighted angiography (SWAN) sequence. Materials and Methods: In the context of a study on brain adaptation mechanisms to hypoxia, 16 healthy men (aged 20–28 years) were studied through magnetic resonance imaging (MRI) under room air conditions, short-term-hypoxia (7 minutes before and during the MRI scan), and long-term hypoxia (8.5 hours before and during the MRI scan). Oxygen saturation was continuously measured using a finger-mounted pulse oximeter. Two independent blinded readers compared the 3 scans of each participant and graded the SWAN source images and minimum intensity projections according to the size, number, and signal intensity of the cerebral veins. Signal intensities of deep cerebral veins were measured, and signal intensity proportions of deep cerebral veins to different parenchymal brain regions were calculated. Results: Nine subjects could be included in the study. In all of them, both readers correctly distinguished the 2 hypoxia scans from the baseline scan, grading the SWAN images acquired under hypoxic conditions as visualizing cerebral veins more prominently. Signal intensities of the deep cerebral veins and signal intensity proportions were significantly lower in the hypoxia scans. No significant differences between short-term and long-term hypoxia were found on visual inspections and signal intensity measurements. This correlated with the results of the pulse oximetry: mean O2 saturation values were 97.9% ± 1.2% (baseline), 84.1% ± 3.8% (short-term hypoxia), and 82.8% ± 4.4% (long-term hypoxia), respectively. Conclusions: Hypoxia leads to visible and measurable changes in cerebral veins as depicted through SWAN. Possible clinical implications of this finding include stroke and tumor imaging and need further investigation.